The Effect of Digital Competence and Partnerships on the Competitiveness of Culinary MSMEs in Kepenuhan District - Rodiana Rodiana; Arfianti Novita Anwar; Hendry Kurniawan (International Journal of Economic and Tourism Research, 2026)
The competitiveness of Micro, Small, and Medium Enterprises (MSMEs) has become an important factor in sustaining business growth in the increasingly competitive digital economy. This study aims to analyze the effect of digital competence and partnership on the competitiveness of culinary MSMEs in Kepenuhan District. The research employed a quantitative approach with an associative design. The population consisted of 34 culinary MSMEs registered in Kepenuhan District, and the sampling technique used was saturated sampling, in which all members of the population were included as research samples. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS software. The results showed that digital competence had a positive and significant effect on competitiveness, with a significance value of 0.001. Partnership also had a positive and significant effect on competitiveness, with a significance value of 0.000. Simultaneously, digital competence and partnership significantly influenced competitiveness, as indicated by the F-test value of 38.401 with a significance level of 0.000. The coefficient of determination showed that both variables explained 69.4% of the variation in competitiveness. These findings indicate that improving digital competence and strengthening partnerships are important strategies to enhance the competitiveness of culinary MSMEs. Strengthening these aspects can help MSMEs expand market access, improve business performance, and adapt to the dynamics of the digital economy.